Choking interventions in sports: A systematic review - Gröpel, P.; Mesagno, C. (International Review of Sport and Exercise Psychology, 2019)
Choking under pressure describes suboptimal sport performance in stressful situations, which has led to two fundamental `choking` models: distraction and self-focus. The purpose of this review was to provide an overview of empirical studies that have tested interventions used to alleviate choking. The systematic review includes 47 empirical studies published up to April 2017, including experimental, quasi-experimental, and single-case studies with athletes. These studies encompassed a variety of interventions (n = 13) that were either distraction based or self-focus based. In addition, a third group - acclimatisation interventions - was identified. The results indicate that, in general, choking interventions based on both choking models and on acclimatisation provide a benefit to performance under pressure. The most reported effective interventions were pre-performance routines, quiet eye training, left-hand contractions, and acclimatisation training. The use of dual task was beneficial for performance under pressure but harmful when used in training. Mixed evidence was found for analogy learning, and null effects were reported for goal setting, neurofeedback training, and reappraisal cues. These results may help athletes and coaches select and implement effective strategies and methods to improve performance under pressure.